A Modification of the Fuzzy Logic Based DASH Adaptation Scheme for Performance Improvement. (5th February 2018) - Kim, Hyun Jun; Son, Ye Seul; Kim, Joon Tae
Abstract : We propose a modification of the fuzzy logic based DASH adaptation scheme (FDASH) for seamless media service in time-varying network conditions. The proposed scheme (mFDASH) selects a more appropriate bit-rate for the next segment by modification of the Fuzzy Logic Controller (FLC) and estimates more accurate available bandwidth than FDASH scheme by using History-Based TCP Throughput Estimation. Moreover, mFDASH reduces the number of video bit-rate changes by applying Segment Bit-Rate Filtering Module (SBFM) and employs Start Mechanism for clients to provide high-quality videos in the very beginning stage of the streaming service. Lastly, Sleeping Mechanism is applied to avoid any expected buffer overflow. We then use NS-3 Network Simulator to verify the performance of mFDASH. Upon the experimental results, mFDASH shows no buffer overflow within the limited buffer size, which is not guaranteed in FDASH. Also, we confirm that mFDASH provides the highest QoE to DASH clients among the three schemes (mFDASH, FDASH, and SVAA) in Point-to-Point networks, Wi-Fi networks, and LTE networks, respectively.